Penerapan Model Pembelajaran Missouri Mathematics Project Pada Materi Himpunan Peserta Didik Kelas Vii Mtsn Nan Sabaris Kabupaten Padang Pariaman - Darma, Sadra; Sepriyanti, Nana (Math Educa Journal, 2018)
The purpose of this research are: to knowing student learning activity during appliying Missouri Mathematics Project Learning Model in mathematics learning and to knowing effect of appliying Missouri Mathematics Project Learning Model to result of mathematics student at VII MTsN Nan Sabaris Padang Pariaman regency, academic year 2016/2017. This research is quasi-experiment with Randomized Control Group Only Design. The population of this research is all student at VII MTsN Nan Sabaris Padang Pariaman Regency. After analysis test of normality, test of homogeneity and test of equity. Sample is collected by using random sampling. The students of class are as experiment class and the students of class are as control class. Based on analysis of this research get student activity during appliying Missouri Mathematics Project Learning Model is improving and average of experiment class is 75,55 and average of control class is 65,22 with using t-test is obtained t hitung > t tabel (3,40>1,64) , α=0,05 . Cause t hitung>t tabel, so H accepted In conclusion, The research result of the Mathematics students at VII MTsN Nan Sabaris Padang Pariaman Regency that is tought by Missouri Mathematics Project learning model is higher than the study result of students at VII MTsN Nan Sabaris that is tought without using Missouri Mathematics Project learning model.Keywords: Student Activity, Mathematics Learning Outcomes, Missouri Mathematics Project learning model